2016
DOI: 10.1016/j.rbmo.2015.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Influence of paternal age on ongoing pregnancy rate at eight weeks' gestation in assisted reproduction

Abstract: A retrospective cohort study was performed with the followings aims: to evaluate the influence of paternal age on best embryo quality available for embryo transfer on the third day; biochemical pregnancy rate; miscarriage rate and ongoing pregnancy rate at 8 weeks' gestational age, after IVF or intracytoplasmic sperm injection (ICSI) treatment, respectively, including treatment with non-ejaculated spermatozoa. In total, 7051 first IVF/ICSI cycles in Radboud university medical center, between 1 January 2001 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
2
20
2
Order By: Relevance
“…Some works suggested a negative correlation between paternal age and fertilization rate (Aboulghar et al, ; Katib, Al‐Hawsawi, Motair, & Bawa, ; Luna et al, ), embryo quality, implantation rate, and pregnancy rate (Belloc et al, ; Bellver, Garrido, Remohí, Pellicer, & Meseguer, ; Frattarelli et al, ; Katib et al, ; Klonoff‐Cohen & Natarajan, ; Luna et al, ; Robertshaw, Khoury, Abdallah, Warikoo, & Hofmann, ; Sharma et al, ). Conversely, others did not find any effect of paternal age on the rates of pregnancy, miscarriage, and live births (Alfaraj & Yunus, ; Alshahrani et al, ; Fernandez‐Gonzalez et al, ; Jaleel & Khan, ; Kong et al, ; Meijerink et al, ; Pérez‐Crespo, Moreira, et al, ; Pérez‐Crespo, Pintado, et al, ; Whitcomb et al, ) especially in first IVF/ICSI cycles (Meijerink et al, ). As many different factors, such as maternal age, ART procedure and semen quality, should be considered when assessing the effects of paternal age on IVF outcomes, these discrepancies could be partially explained by the different study protocols/populations.…”
Section: Discussionmentioning
confidence: 98%
“…Some works suggested a negative correlation between paternal age and fertilization rate (Aboulghar et al, ; Katib, Al‐Hawsawi, Motair, & Bawa, ; Luna et al, ), embryo quality, implantation rate, and pregnancy rate (Belloc et al, ; Bellver, Garrido, Remohí, Pellicer, & Meseguer, ; Frattarelli et al, ; Katib et al, ; Klonoff‐Cohen & Natarajan, ; Luna et al, ; Robertshaw, Khoury, Abdallah, Warikoo, & Hofmann, ; Sharma et al, ). Conversely, others did not find any effect of paternal age on the rates of pregnancy, miscarriage, and live births (Alfaraj & Yunus, ; Alshahrani et al, ; Fernandez‐Gonzalez et al, ; Jaleel & Khan, ; Kong et al, ; Meijerink et al, ; Pérez‐Crespo, Moreira, et al, ; Pérez‐Crespo, Pintado, et al, ; Whitcomb et al, ) especially in first IVF/ICSI cycles (Meijerink et al, ). As many different factors, such as maternal age, ART procedure and semen quality, should be considered when assessing the effects of paternal age on IVF outcomes, these discrepancies could be partially explained by the different study protocols/populations.…”
Section: Discussionmentioning
confidence: 98%
“…The effect of the age difference between the male and female partner ages (Δ = M age -F age ) that gave OR Δ = 1.04 (CI 95% :1.0–1.08) pointing out the rising probability of pregnancy when the female partner is younger is noticeable. In the present study, according to Meijerink et al (16), we used the probability of obtaining only one or no type A embryo (N A ≤1) as a negative indicator to evaluate the reduced efficacy of the biological outcome. The probability of N A ≤1 increases with both male and female age (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, in women aged 30–34 years old, the implantation rate dropped with increasing paternal age and the pregnancy rate was significantly higher with male partners aged <30 years or 30–32 years compared to men aged 36–38 or 39–41 years. Meijerink et al (16) conducted a retrospective study on 7,051 IVF/ICSI cycles. They did not found any statistically significant difference in pregnancy rate for men aged 35–44 years or for men ≥45 years compared to the control group of men <35 years.…”
Section: Discussionmentioning
confidence: 99%
“…Since that review, a number of larger cohort studies have been performed, however, the results of these studies have been contradictory. Some studies have found that paternal age has a detrimental effect on outcome (19)(20)(21)43) and others have not found evidence of a detrimental effect (21,30,44,45). A systematic review of studies performed using the donor egg model suggested that advancing paternal age is not associated with adverse oocyte donation outcomes (17).…”
Section: Discussionmentioning
confidence: 99%